New fractional model to analyze impacts of Newtonian heating, shape factor and ramped flow function on MgO–SiO2–Kerosene oil hybrid nanofluid. (October 2022) - Asifa,; Anwar, Talha; Kumam, Poom; Muhammad, Shah
Abstract: In modern times, diathermal oils have piqued the attraction of various researchers due to their multiple significant industrial applications. The present work aims to investigate the heat transfer performance of a specific diathermal oil called kerosene oil (Ko) based hybrid nanofluid. Magnesia ( MgO ) and silica ( SiO 2 ) nanoparticles are involved in the hybridization process for the preparation of the required hybrid nanofluid. This study not only evaluates synergistic features of nanoparticles but, also focuses to provide a comparative analysis for five different shapes like hexahedron, column, tetrahedron, spherical, and lamina. The primary mathematical model is composed of coupled flow and temperature equations. In this work, the performance of a hybrid nanofluid is first time examined for the simultaneous imposition of Newtonian heating and ramped boundary flow function. To shift the model in a fractional framework, generalization of Fourier law is obtained by making use of Prabhakar fractional operator. Exact solutions for both fractional and classical cases are determined by first introducing some unit-free variables and then treating consequent equations with the Laplace transform. To cover all aspects of the considered problem, these solutions are elucidated in the form of graphs, and the contribution of each factor is discussed with physical explanations. Moreover, numerical outcomes of Nusselt number are tabulated to analyze % augmentation, and dominance of shape characteristics, volume fraction, and fractional parameters on the thermal efficiency of working hybrid nanofluid. Numerical computations of skin friction coefficient are also communicated to inspect variations in shear stress corresponding to several phenomena. The hybridization of kerosene oil with MgO and SiO 2 nanoparticles is anticipated to improve its thermal efficacy by 40.14%, which certainly enhances its industrial usefulness. The escalating volume proportion of nanoparticles leads to reducing the flow velocity. Moreover, for small values of time, velocity and temperature are increasing functions of fractional parameters.